COVID-19 among Healthcare Workers of Teaching Hospitals Affiliated with Rawalpindi Medical University - Muhammad Umar , Rizwana Shahid , Muhammad Mujeeb Khan ,Shazia Zeb ,Fatima Rauf , Uzma Hayat (Journal of Rawalpindi Medical College, 2021)
Objectives: To overview COVID-19 scenario among healthcare workers in teaching hospitals of Rawalpindi Medical University Subjects & Methods: A cross-sectional descriptive research was done among 482 coronavirus infected healthcare professionals from three teaching hospitals (Holy Family Hospital, Benazir Bhutto Hospital and District Head Quarters) that were affiliated with Rawalpindi Medical University during January 2021. Healthcare workers with COVID confirmation via RT-PCR testing reports were included in the study through consecutive sampling. Their demographic profile, workplace attributes, clinical manifestations, oxygen saturation, source of infection, re-infection, hospitalization, requirement for oxygen supply and disease severity according to COVID-19 adult cases categorization were inquired. Data analysis was done by means of SPSS version 25.0. Results: Mean age of 482 healthcare workers was 29.6 ± 5.7 years. Mainstream (69.1%) of our study participants was constituted by female healthcare staff. Majority (34%) were postgraduate trainees followed by 29% nurses and 20% house officers. Mean duration of sickness was 13.6 ± 6.4 days. About 63.1% of study subjects were COVID infected during July –December 2020. About 4.8% healthcare personnel were asymptomatic and 78% caught infection from their workplace. Approximately 82% suffered from fever while 71.4% and 55.8% went through bodyaches and cough respectively. Out of 39 hospitalized workers, 23 required oxygen supply for their vitality. Severe COVID infection was determined only among 5.4% healthcare professionals. Conclusion: Healthcare workers are more susceptible to acquire COVID infection from their workplace. In view of this vulnerability, firm compliance to preventive measures against coronaviurs infection by healthcare staff and general public is deemed necessary for their viability.